2005
DOI: 10.1101/gad.1317105
|View full text |Cite
|
Sign up to set email alerts
|

Nascent peptide-mediated translation elongation arrest coupled with mRNA degradation in the CGS1 gene of Arabidopsis

Abstract: Expression of the Arabidopsis CGS1 gene that codes for cystathionine ␥-synthase is feedback regulated at the step of mRNA stability in response to S-adenosyl-L-methionine (AdoMet). A short stretch of amino acid sequence, called the MTO1 region, encoded by the first exon of CGS1 itself is involved in this regulation. Here, we demonstrate, using a cell-free system, that AdoMet induces temporal translation elongation arrest at the Ser-94 codon located immediately downstream of the MTO1 region, by analyzing a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 45 publications
5
143
0
1
Order By: Relevance
“…Some regions likely encode nascent peptides which can stall ribosomes during translation elongation as the MTO1 region in CGS1 or are upstream of structured regions that can block the movement of ribosomes (Onouchi et al, 2005). The one with the last peak of 59-truncated RNA ends located 16 nucleotides upstream of main ORF stop codons as in the degradation pattern observed in CPuORFs may cause ribosome pausing during translation termination.…”
Section: Analysis Of the Rna Degradome Allows Dissection Of Ribosome mentioning
confidence: 99%
See 1 more Smart Citation
“…Some regions likely encode nascent peptides which can stall ribosomes during translation elongation as the MTO1 region in CGS1 or are upstream of structured regions that can block the movement of ribosomes (Onouchi et al, 2005). The one with the last peak of 59-truncated RNA ends located 16 nucleotides upstream of main ORF stop codons as in the degradation pattern observed in CPuORFs may cause ribosome pausing during translation termination.…”
Section: Analysis Of the Rna Degradome Allows Dissection Of Ribosome mentioning
confidence: 99%
“…Besides CPuORFs, the nascent peptide encoded by a CDS region in the first exon of Arabidopsis CGS1, known as the MTO1 region, has been reported to block ribosome elongation and induce RNA decay in response to S-adenosyl-L-methionine (AdoMet) (Onouchi et al, 2005). Similar to the degradation fragments we observed in bZIP CPuORFs (Figure 2), Haraguchi et al (2008) detected a ladder of truncated 59 termini separated in length by ;30-nucleotide increments in the MTO1 region together with the 59 upstream region after treatment with AdoMet.…”
Section: Ribosome Stacking Was Predicted In Cdss Using the Rna Degradmentioning
confidence: 99%
“…Significant advances in our understanding on the regulation of the methionine biosynthetic pathway in plants were provided through the isolation and characterisation of genetic mutants in which methionine accumulation is altered Chiba et al 1999;Bartlem et al 2000;Goto et al 2002;Shen et al 2002;Onouchi et al 2005), as described in further detail below.…”
Section: Recycling Of Methioninementioning
confidence: 99%
“…De novo Met synthesis consists of three consecutive reactions localized in plastids (4) and catalyzed by cystathionine ␥-synthase, cystathionine ␤-lyase, and methionine synthase. Several recent studies have indicated that Met synthesis and accumulation are subject to complex regulatory controls in which cystathionine ␥-synthase plays a crucial role (5)(6)(7).…”
mentioning
confidence: 99%